Implementasi Corporate Social Re Implementasi Corporate Social Responsibility PT. Angkasa Pura I Makassar Berbasis Pemberdayaan Ekonomi Masyarakat - Setiyawati, Dewi; Semaun, Syahriyah; Muhammadun , Muzdalifah (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
The purpose of this research is to examine the implementation of Corporate Social Responsibility of PT. Angkasa Pura I Makassar based on Community Economic Empowerment. This type of research uses qualitative methods. The results of this study will be described in a descriptive narrative form. The approach in this study is to use a phenomenological approach. The primary data from this study is data from interviews with informants in the study. Likewise other data related to research subjects, both the results of observations and the results of documentation. The results of this study were compiled using systematic data reduction, data display and drawing conclusions. The conclusion of the research shows that the implementation of CSR at PT. Angkasa Pura I Makassar departs from the planning stage, namely the stage of analyzing the needs of the surrounding community and finding relevant programs. Next is the implementation stage, namely the CSR implementation stage which is based on the initial plan. The last is the evaluation and reporting stage, in this stage it is evaluated and reported regarding the factual conditions in the field for future improvements. Corporate Social Responsibility System PT. Angkasa Pura I Makassar is based on the needs of the community around the company's environment with an easy submission system and can be reached by all groups of people.